2016
DOI: 10.3892/mco.2016.923
|View full text |Cite
|
Sign up to set email alerts
|

Role of short-term follow-up magnetic resonance imaging in the detection of post-operative residual breast cancer

Abstract: The aim of the present study was to evaluate the role of short-term follow-up magnetic resonance imaging (MRI) in the detection of postoperative residual breast cancer. A retrospective analysis was performed on 10 patients who were diagnosed with non-malignant breast lesions by preoperative clinical, ultrasound and mammography examinations and intraoperative frozen-section pathology. These patients were finally confirmed as having malignant breast lesions by paraffin-embedded tissue histology and corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a study that assessed CVD-related prognoses due to differences in the mechanism of weight loss, it was found that the effects of intentional and unintentional weight loss might be different [19]. Intentional weight reduction, such as decreasing calorie intake and increasing physical activity, had a positive effect on CVD risk, and the benefit increased with increased weight loss, especially in obese Caucasian women [7,20,21]. Nevertheless, whether intentional or unintentional, weight loss had a negative effect on the CVD outcome in older Caucasian men [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that assessed CVD-related prognoses due to differences in the mechanism of weight loss, it was found that the effects of intentional and unintentional weight loss might be different [19]. Intentional weight reduction, such as decreasing calorie intake and increasing physical activity, had a positive effect on CVD risk, and the benefit increased with increased weight loss, especially in obese Caucasian women [7,20,21]. Nevertheless, whether intentional or unintentional, weight loss had a negative effect on the CVD outcome in older Caucasian men [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the weight loss group contained a higher proportion of elderly subjects as well as underlying diseases associated with frailty, such as ischemic heart disease, chronic obstructive pulmonary disease, and chronic kidney disease. In a study by Look AHEAD researchers, two-thirds of participants with a moderate to large intentional weight loss (more than 3%) showed a partial or whole weight regain [21]. It was reported that weight regain after diet-induced intentional weight loss weakened any cardiovascular benefits obtained by weight loss [27].…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 Postoperative MRI after surgical management of breast cancer is less commonly utilized in infrequent cases of potential residual breast tissue or in the work-up of palpable masses. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%